Shoulder instability in the tennis player: arthroscopic approach and thermal capsulorrhaphy - Tibone, J. (1999)
Shoulder instability in the tennis player develops as a result of repetitive microtrauma from serving and overhead actions. There is anterior instability, due to a stretched anterior capsule. If the arthroscopic findings are minimal with a positive drive-through sign, but no Bankart or Hill Sachs lesion, thermal capsulorrhaphy may be considered. Indications are 6 months of failed conservative care, including strengthening of the rotator cuff and scapular stabilisers. Thermal capsulorrhaphy is based on the collagen properties of a rigid triple helical structure that transforms into a random coil with heating. Histologic examinations show loss of the periodic cross-striations and increases in fibril diameter. The amount of shrinkage depends on the temperature. Generally, 65-75 degrees are ideal. The heat can be delivered using a laser beam or a radio frequency signal. The technique consists of a posterior arthroscope with the probe anterior and heating the medial and inferior gleno-humeral ligament. Post-operative management consists of a sling for 1-2 weeks, the avoidance of passive stretching in rehab, no weights for six weeks, and return to sport at 12 weeks. Complications are rare, but one should be careful not to damage the axillary nerve when heating the inferior capsule between 5 and 7 o`clock. No clinical studies have been published yet. Preliminary results of laser studies by the author are promising. His two-year follow-up data of the radio frequency studies have a success rate of 90%.